Motivation and generative artificial intelligence: perceived benefits among advertising and multimedia students - Ygnacio Tomaylla-Quispe; Fanny Paredes-Quispe; María del Pilar Ponce; Luis Melgar-Amado (Institute of Advanced Engineering and Science, 2026)
This study aimed to examine how intrinsic and extrinsic motivation, along with the use of and exposure to generative artificial intelligence (GenAI), influence the educational benefits perceived by students in disciplines linked to digital creativity and visual communication, namely graphic design, advertising, and multimedia. A quantitative, correlational and non-experimental design was used. The data was collected online during the 2024 academic year through a validated survey administered to 203 college students selected by convenience sampling. An instrument based on and adapted from previous studies was used to measure intrinsic and extrinsic motivation, perceived benefits, and creative use of GenAI tools. The answers were collected with a five-item Likert scale. The relationships between the variables were analyzed with the partial least squares structural equation modeling (PLS-SEM) procedure using the SmartPLS 4. The results indicate that both intrinsic and extrinsic motivation positively influence perceived benefits. These findings highlight the educational impact of GenAI on creative disciplines and highlight the need for academic programs and education policy directors to promote its responsible adoption, ensuring that students gain the skills and confidence to use these technologies effectively.